A Multi-Objective Optimization Model for Home Health Care Routing and Scheduling with a Case Study - Rosyidi, Cucuk Nur; Ramadandhyna, Annisa Puja; Laksono, Pringgo Widyo (Institute of Research and Community Outreach - Petra Christian University, 2023)
Home health care (HHC) is a health service provided by a hospital so that patients can be taken care of at their homes. Assigning multiple caregivers to serve patients during working hours is one of the main issues in HHC planning. In this study, multi-objective mixed-integer nonlinear programming was formulated for HHC daily planning. The model aims to simultaneously minimize total service time, total traveled distance, total cost comprising the opportunity loss from unvisited patients and penalty cost due to the violation of gender preference, and total carbon emissions generated by the caregiver’s vehicle. Using real data from Dr. Moewardi Hospital, a case study was provided in order to show the applicability of the model. The model can be utilized to assist the HHC coordinator in determining the optimal schedule and routing of HHC visits.